The spread of novels : translation and prose fiction in the eighteenth century - McMurran, Mary Helen, 1962- (Translation/transnation., 2010)
Fiction has always been in a state of transformation and circulation: how does this history of mobility inform the emergence of the novel? The Spread of Novels explores the active movements of English and French fiction in the eighteenth century and argues that the new literary form of the novel was the result of a shift in translation. Demonstrating that translation was both the cause and means by which the novel attained success, Mary Helen McMurran shows how this period was a watershed in translation history, signaling the end of a premodern system of translation and the advent of modern li.